Mali : Poverty Reduction and Strategy Paper-2010 Progress Report. (IMF Staff Country Reports; Country Report, 2011)
This 2010 Progress Report on the Poverty Reduction Strategy Paper (PRSP) focuses on the poverty condition in Mali. The incidence of poverty in Mali fell from 55.6 percent in 2001 to 43.6 percent in 2010. Over the past decade, poverty has fallen in rural areas, in Bamako, and in other urban areas. However, it increased in Bamako and in other urban areas between 2006 and 2010. The government has reaffirmed its commitment to accelerate economic growth, to make Mali an agricultural power by 2015, and to combat poverty effectively.